Bombesin-Like, Substance P and Vasoactive Intestinal Polypeptide Receptors in Fetal Cortical Homografts to Host Cortex and Spinal Cord. Issue 3 (1989) - Moody, Terry W.; Getz, Reina L.; Goldberg, William J.; Bernstein, Jerald J.
Abstract : Neuropeptide receptors were visualized in homografts of fetal cortex (E14) into adult rat cortex (immediate or 7 day delay) and spinal cord using in vitro autoradiographic techniques to explore the expression of peptide receptors in the same graft tissue in different central nervous system implantation sites. Receptors for bombesin (BN)-like peptides developed in the grafts by 3 weeks postimplantation regardless of location or age of implantation pocket in host. After 4 weeks, the density of BN receptors was confined to the graft. In grafts to spinal cord, however, high densities of BN-like receptors were not confined to the graft but were distributed throughout the spinal cord. In contrast, the density of vasoactive intestinal polypeptide (VIP) and substance P (SP) receptors was moderate and low to undetectable in the fetal grafts. The development of the peptide receptors studied was graft donor tissue specific since they were not altered by central nervous system implantation site.